Step-by-step explanation:
A. gof=g(f(x))
= g(f(6))
=6×6
36
Answer:
15
Step-by-step explanation:
1- 6-x=9 Place the terms on the correct side; always place terms with x on the left hand side and the others on the right hand side. (when placing on the other side convert from + to - or reversed) (the 6- converted to 6+)
2- x= 6+9= 15 Now work out the sum.
3- x= 15
Answer:
I think that is enlargement
Step-by-step explanation:
i like helping out people oh by the way i'm new will you be my friend
Given that,
Shelley's pet food store sold one customer 5 peanut butter biscuits for $3. She sold another customer 7 beef treats for $4.20.
For peanut, the cost is ratio is
![\dfrac{5}{3}](https://tex.z-dn.net/?f=%5Cdfrac%7B5%7D%7B3%7D)
For beef, the ratio is
![\dfrac{7}{4.2}](https://tex.z-dn.net/?f=%5Cdfrac%7B7%7D%7B4.2%7D)
If we take cross product of these items,
![\dfrac{5}{3}=\dfrac{7}{4.2}\\\\5\times 4.2=3\times 7\\\\21=21](https://tex.z-dn.net/?f=%5Cdfrac%7B5%7D%7B3%7D%3D%5Cdfrac%7B7%7D%7B4.2%7D%5C%5C%5C%5C5%5Ctimes%204.2%3D3%5Ctimes%207%5C%5C%5C%5C21%3D21)
It implies, that the sale is in true proportion. From the cross product, we find that it is equal.
Answer:
add me on snap kingmadness7062
Step-by-step explanation: